Surface currents modeling based on tidal cycles and monsoon in tropical estuary, Indonesia. Issue 1 (October 2021) - Najamuddin,; Prartono, T; Sanusi, H S; Nurjaya, I W; Pembonan, R E; Umasangaji, H; Mutmainnah,; Tahir, I; Inayah,
Abstract: The modeling uses a software-based numerical model DHI MIKE user interface developed by The Danish Hydraulic Institute (DHI) Water and Environment, Denmark. Simulation of current uses a 2-dimensional model (averaging to depth) with a finite element approach. Modeling of currents was conducted to know current dynamics by tidal cycle and seasonal variation (west and east monsoon). The models were validated using correlation coefficient value (r) by comparing direct measurement and model output. The r-value for current velocity during west monsoon was 0.653 and east monsoon was 0.697 and for current direct during west monsoon was 0.887 and the east monsoon was 0.857. While the r-value for the tide was 0.858. All these r values showed a strong correlation and these indicated the models were valid. The result of the simulation of the current models showed that the surface currents were strongly influenced by the tidal cycles. The currents direct flowed to the south at flood tide and to the eastern at ebb tide. The maximum current velocity during the west monsoon was 0.50 m/sec and during the east monsoon was 0.40 m/sec. The averages of currents direct were more dominant eastward of Jeneberang estuary.